Additive manufacturing of an aluminum matrix composite reinforced with nanocrystalline high-entropy alloy particles - Karthik, G.M.; Panikar, Santhanu; Ram, G.D. Janaki; Kottada, Ravi Sankar (Materials science & engineering. A, Structural materials : properties, microstructure and processing, 2017)
In the present work, a metal-metal composite consisting of aluminum-magnesium alloy AA5083 matrix and nanocrystalline CoCrFeNi high-entropy alloy reinforcement particles in 12vol% was successfully friction deposited in multiple layers. The layer interfaces or the reinforcement/matrix interfaces showed no brittle intermetallic formation – thanks to the inert nature as well as the high strength and hardness of the high-entropy alloy reinforcement particles. The composite showed significantly higher tensile and compressive strengths as compared to standard wrought-processed alloy AA5083-H112 and offered a much better combination of strength and ductility when compared to conventional aluminum matrix composites reinforced with ceramic particles. The current study establishes friction deposition as a viable technique for additive manufacturing of novel high-performance composite materials.